The Challenges of Dealing with Nitrogen Pollutants in Groundwater - Zarama-Alvarado, Stephanye (Revista Científica, 2018)
Nitrogen compounds are being injected into the environment by human activities, which are altering the global nitrogen cycle and, thus, water systems. There is principally serious growing concern about the actual environmental consequences of the nitrogen pollutants in groundwater since a safe supply of clean water is needed for human consumption. Recent observations in the field of measurements and studies in the laboratory suggest that there are limitations of effective methods that detect and quantify biogeochemical reactions of nitrogen loss occurred in this aquatic body. This review explores our understanding of nitrogen pollutants on groundwater, taking into consideration the biogeochemical reactions of nitrogen cycle, and the limitations and advantages of analytical methods used in the detection of nitrogen compounds.